Application of the real-time pcr for the detection and enumeration of vibrio parahaemolyticus from selected shrimp pond - Yusuf, I. (Universiti Malaysia Sarawak, UNIMAS, 2013)
Vibrio parahaemolyticus is a rod shaped, gram negative bacterium. It is an obligate halophile usually found in the marine environment. The bacterium has been the major cause of food poisoning and gastroenteritis in many countries like the US and Japan. In this study, water samples was collected from selected shrimp ponds (Asia Aquaculture Sdn. Bhd) in Bako, Sarawak and analyzed with real-time PCR using SYBR green chemistry to detect and enumerate the V. parahaemolyticus population in the water samples. We had performed these analyses to investigate the dynamic of V. parahaemolyticus throughout the shrimp culture period. At the end of the project, the dynamic of V. parahaemolyticus shows a decreasing population for pond 1 and increasing population for pond 14. The results show that R2 value for pond 1 was 0.3073 and pond 14 was 0.3735. It is considered that real-time PCR assay allows more rapid detection and identification of V. parahaemolyticus which is faster than current conventional assay.